EFEKTIVITAS SOFTWARE “MOBILE ELECTRONIC LAW’S DICTIONARY”SEBAGAI UPAYA PENINGKATAN PEMAHAMAN TERHADAPISTILAH HUKUM BAGI MAHASISWA JURUSAN HUKUM - Shelly Aprillia, Lina Priharyanti, Nafngan Fitriansah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
Mobile Application Based Mobile Electronic Law’s Dictionary Software as learning media for lawstudents served as a solution and innovation in overcoming the problem of understanding legal terms.The aims of the research were 1) designing and producing Mobile Electronic Law’s Dictionary Software”,2) revealing the performance of Mobile Electronic Law’s Dictionary Software, and 3) finding out the useand strength of Mobile Electronic Law’s Dictionary Software.The reserach were conducted through several steps, namely 1) Need Identification 2) SoftwareDesign and Production, 3) Software Coding, 4) Software Specification, 5) Software Testing, and 6)Revision and Operation.The results showed was Mobile Electronic Law’s Dictionary Software. The results of thequestionnaires and interviews could be used as reference to improve the understanding of various legalterms, especially for law students. It was important because the data from the questionnaires neededattention and follow up.Key words : Mobile Electronic Law’s Dictionary, Software, legal terms